Application Of The Discovery Learning Model In Improving English Learning Activities and Outcomes In Class VIII Students Of SMPN 9 Kendari - Mukti Ramadhan (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2023)
This study aims to increase student learning activities and outcomes in social studies subjects through the This study aims to increase student learning activities and outcomes in English subjects through the application of discovery learning models. This research was conducted in class VIII of SMP Negeri 9 Kendari in the even semester of the 2021/2022 Academic Year. The subjects studied were students in class VIII-5, totaling 34 students, with details of 17 male students and 17 female students. The factors observed in this study are student factors. This research was carried out in 2 (two) cycles, including: a) planning; b) implementation of actions; c) observation, d) reflection. The data obtained in this study were analyzed using descriptive statistics. The results of the study show that the discovery learning model in the implementation of English learning can improve learning outcomes and activities of class VIII-5 students at SMP Negeri 9 Kendari in accordance with what has been planned, the application of this learning method has provided experience for teachers and students so that the learning atmosphere in in the classroom more lively and interesting and give a meaningful impression on students. This can be seen in the test scores of students starting from cycle I to cycle II which continue to experience a definite increase. As for the achievement of the average class evaluation value, namely in the first cycle the average value was 73.09 and in the second cycle it increased to 83.82. Class classical completeness in cycle I was 61.76% and in cycle II it increased to 91.18%.